A probable pre-main sequence chemically peculiar star in the open cluster Stock 16 - Netopil, M. (2014)
We used the Ultraviolet and Visual Echelle Spectrograph of the ESO-Very Large Telescope to obtain a high resolution and high signal-to-noise ratio spectrum of Stock 16-12, an early-type star which previous Δa photometric observations suggest being a chemically peculiar (CP) star. We used spectral synthesis to perform a detailed abundance analysis obtaining an effective temperature of 8400 ± 400 K, a surface gravity of 4.1 ± 0.4, a microturbulence velocity of 3.4 +0.7−0.3 −0.3+0.7 km s−1, and a projected rotational velocity of 68 ± 4 km s−1. We provide photometric and spectroscopic evidence showing the star is most likely a member of the young Stock 16 open cluster (age 3–8 Myr). The probable cluster membership, the star's position in the Hertzsprung–Russell diagram, and the found infrared excess strongly suggest the star is still in the pre-main-sequence (PMS) phase. We used PMS evolutionary tracks to determine the stellar mass, which ranges between 1.95 and 2.3 M⊙, depending upon the adopted spectroscopic or photometric data results. Similarly, we obtained a stellar age ranging between 4 and 6 Myr, in agreement with that of the cluster. Because the star's chemical abundance pattern resembles well that known of main sequence CP metallic line (Am) stars, the object sets important constraints to the diffusion theory. Additional spectroscopic and spectropolarimetric data allowed us to conclude that the object is probably a single non-magnetic star.